Improving the uptake of newborn screening for endocrinopathies and inborn errors of metabolism: A quality improvement initiative. Issue 1 (February 2020) - Varghese, N; Joshi, P; Cecilia, M; Gupta, N; Agarwal, R; Kabra, M; Deorari, Ak
Abstract: Introduction: Newborn Screening (NBS) is a globally recognized essential, preventive public health program for identifying life threatening and debilitating conditions. Method: This single centre quality improvement (QI) initiative was taken to improve the newborn screening uptake from the existing rate of 70%–100% over a period of three months in a tertiary care facility of India. A QI team was constituted to evaluate the reasons for low uptake of NBS and introduce changes in the existing system of NBS. Results: Baseline data collection along with process mapping, and fishbone analysis were done. Problems attributing to most of the missed cases of newborns were studied using Pareto chart. Total three plan-do-study-asct (PDSA) cycles were used to fix the identified problems in order to improve the rate of NBS. The results of PDSA cycles were discussed among the team members. Frequency and percentage was computed for the collected data, after coding and entering in excel sheet. . Conclusion: The QI project on NBS successfully improved the rate of uptake of newborns for NBS from baseline to 100%.